Permintaan Kopi Indonesia: Studi Terhadap Dua Negara Tujuan Utama Ekspor - Cia Cai Cen; Erwin Nuryana Faisal (Universitas Pasundan, 2021)
On a global scale, Indonesia is ranked the fourth largest in the world after Brazil, Vietnam and Colombia. Therefore, Indonesia has the goal of the largest coffee export market that is in demand by the United States (USA), which reached a total export from 2000 to 2018 of 1,159,877 tons or reached a share of 15.43% with a total export value of USD 3.42 billion. And followed by Japan with a market share reaching 12.65% which is equivalent to 951,022 tons or reaching a total export value of USD 1.75 billion. This study examines the factors of Indonesian coffee demand for two main export destination countries, namely Japan and America. Demand for Indonesian coffee in the American market is affected by GDPA and HKRD in the long term, and HKRD in the short term. Then the demand for Indonesian coffee in the Japanese market is influenced by the KURSJ, HKAD, and HKK in the long term, and the KURSJ and HKK in the short term.